Variety and Digestibility of Forages Fed to Sacrificial-goats: A Preliminary Study in Mataram City - Suhubdy Suhubdy; Sofyan D. Hasan; Ryan Aryadin Putra (Postgraduate, University of Mataram, 2023)
The study evaluated the variety and digestibility of forages fed to sacrificial-goats in Mataram. The study was carried out by direct observation method. A total of 20 points vendors selling sacrificial goats were used as sampling locations. From all stall selling point, all types of forage as feed were collected. The collected feed samples were identified and tested for digestibility. The results showed that Turi (Sesbania glandiflora) leaves had the highest Dry Matter Digestibility (DMD), which was 65.54%, compared to the DMD of other forage samples, while the lowest DMD was obtained of Gayam (Inocarpus fagifer) leaves, which was 24.86% (P<0.05). As with the DMD value, the highest organic matter digestibility (OMD) was by Turi (61.08%) and the lowest OMD obtain by Gayam which had an OMD value of 11.85% (P<0.05). The OMD of Waru leaves (48.68%) was not different but does not show any difference of Ketapang (Terminalia catappa) leaves (44.73%). It was concluded that among the ten forages offered by vendor to sacrificial-goats; by order of their digestibility, Turi (Sesbania glandiflora), Waru, (Hibiscus tiliaceus), and Ketapang (Terminalia catappa) leaves produced the highest DMD and OMD.